Radiographic image analysis of Anacardium othonianum Rizz (anacardiaceae) achenes subjected to desiccation - Silva, Lílian Abadia da; Sales, Juliana de Fátima; Neves, José Maria Gomes; Santos, Heloísa Oliveira dos; Silva, Glicélia Pereira (Acta Scientiarum. Agronomy, 2017)
Studies evaluating the internal morphology and seed quality of native species are essential for successful conservation programs. Our aim was to verify the efficiency of X-ray imagery in evaluating cashew-tree-of-the-cerrado (Anacardium othonianum Rizz.) achene viability after desiccation. The achenes were collected at 12% water content (w.b.) and dried in silica gel until they reached 10, 8, 6, and 4% (w.b.). The fruit morphology and the quality of the seeds were evaluated by X-ray test together with vigor, electrical conductivity and emergence tests. Achenes with different water contents were exposed to an X-ray machine at 18 kV for 11 s and were thereafter submitted to emergence tests. The images were analyzed, and the achenes were classified based on internal morphology as completely full, malformed, or empty. These results were compared to those from the emergence tests. The statistical design was a complete randomized factorial (5 x 3). Desiccation to 4% (w.b.) did not damage or modify the internal structures. X-ray was efficient in evaluating the internal morphology and detecting achene quality, making it possible to remove empty and abnormal fruit and form vigorous seed lots, reducing the cost of storage and bedding plant production for this native species.